2005
DOI: 10.1038/modpathol.3800259
|View full text |Cite
|
Sign up to set email alerts
|

Utility of D2-40, a novel mesothelial marker, in the diagnosis of malignant mesothelioma

Abstract: Although immunohistochemistry has proven to be valuable in the differentiation of epithelioid mesothelioma from pulmonary or metastatic adenocarcinoma, no single antibody has demonstrated absolute sensitivity or specificity in making this distinction. Using immunohistochemical analysis with D2-40, a recently available monoclonal antibody that has been used as a lymphatic endothelial marker, we examined 53 cases of mesothelioma, 28 cases of reactive pleura, 30 cases of pulmonary adenocarcinoma, 35 cases of rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
199
3
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(222 citation statements)
references
References 20 publications
17
199
3
3
Order By: Relevance
“…5,7,15,[18][19][20]33 The D2-40 staining frequency is also controversial in sarcomatoid and biphasic malignant mesothelioma. Whereas Chu et al 23 reported staining in all types of malignant mesothelioma, Ordóñ ez 24 did not detect any D2-40 staining in either sarcomatoid malignant mesothelioma or sarcomatoid areas of biphasic malignant mesothelioma.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…5,7,15,[18][19][20]33 The D2-40 staining frequency is also controversial in sarcomatoid and biphasic malignant mesothelioma. Whereas Chu et al 23 reported staining in all types of malignant mesothelioma, Ordóñ ez 24 did not detect any D2-40 staining in either sarcomatoid malignant mesothelioma or sarcomatoid areas of biphasic malignant mesothelioma.…”
mentioning
confidence: 84%
“…5,21,22 In addition to calretinin, D2-40 has been recently recommended as a new marker for malignant mesothelioma. 23,24 D2-40 is a novel monoclonal antibody that was reported to recognize a 40 kDa surface sialoglycoprotein expressed in germ cell neoplasia and fetal testicular gonocytes. 25 A recent investigation has demonstrated that this mucin-type glycoprotein is podoplanin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12 The broad application of D2-40 immunohistochemistry has established reactivity to multiple cell lineages and tumors such as mesothelioma, ovarian serous carcinoma, schwannoma, meningioma, synovial sarcoma, gastro-intestinal stromal tumor, leiomyosarcoma and others. [24][25][26] It is unknown whether D2-40 immunoreactivity in a wide spectrum of normal and neoplastic cells is due to a single protein expressed in these various tissues or results from a crossreactivity with multiple surface glycoproteins sharing the D2-40-recognized epitope defined by the common carbohydrate core. It is also unknown whether D2-40 reacts with the same or different antigens in normal lymphatics and in vascular tumor cells.…”
Section: D2-40 In Kaposiform Hemangioendotheliomamentioning
confidence: 99%
“…[10][11][12] D2-40, a marker of lymphatic endothelium as well as benign and malignant mesothelial cells, and a specific high molecular cytokeratin (CK) 5/6 were considered as useful 'mesothelioma markers'. [12][13][14][15] The aim of this study is to characterize the expression 'mesothelioma markers' and a panel of biological markers by serous tumors of the female genital tract and to explore possible variation in expression of markers among different sites.…”
mentioning
confidence: 99%